Adjuvant CDK4/6 inhibitors in early‐stage breast cancer: Clinical evidence and considerations for risk stratification and treatment selection - Austin D. Williams; Anna Weiss (Cancer, 2026)
Abstract Hormone receptor–positive, human epidermal growth factor receptor 2–negative breast cancer is the most common biologic subtype and carries a persistent risk of recurrence, particularly in patients with high‐risk, early‐stage disease. Cyclin‐dependent kinase 4 and 6 inhibitors, initially established as a standard component of first‐line therapy in the metastatic setting based on improvements in progression‐free and overall survival, have since been evaluated in the adjuvant setting. While adjuvant palbociclib did not improve invasive disease‐free survival, the monarchE and NATALEE trials demonstrated that abemaciclib and ribociclib, respectively, reduce recurrence risk in patients with high‐risk, early‐stage disease, with emerging overall survival data further supporting their use. However, the absolute magnitude of benefit varies substantially with baseline risk, and treatment‐related toxicity and adherence challenges must be considered, as approximately 20% to 25% of patients discontinue therapy before completion. The integration of these agents into clinical practice also intersects with ongoing efforts to deescalate axillary surgery, as treatment eligibility has been largely defined by anatomic staging, particularly nodal status. Available data suggest that the incremental impact of axillary surgery on identifying candidates for cyclin‐dependent kinase 4 and 6 inhibition is modest, especially among the favorable‐risk populations now eligible for surgical deescalation. As the field evolves, advances in molecular risk stratification, genomic profiling, and dynamic biomarkers are poised to shift treatment selection from anatomic staging toward biologically driven approaches. Multidisciplinary decision‐making that integrates tumor biology, anticipated absolute benefit, toxicity, patient preferences, and surgical considerations will be essential to ensure individualized care.